3′-End labeling of nucleic acids by a polymerase ribozyme. Issue 17 (13th June 2018) - Samanta, Biswajit; Horning, David P; Joyce, Gerald F
Abstract: A polymerase ribozyme can be used to label the 3′ end of RNA or DNA molecules by incorporating a variety of functionalized nucleotide analogs. Guided by a complementary template, the ribozyme adds a single nucleotide that may contain a fluorophore, biotin, azide or alkyne moiety, thus enabling the detection and/or capture of selectively labeled materials. Employing a variety of commercially available nucleotide analogs, efficient labeling was demonstrated for model RNAs and DNAs, human microRNAs and natural tRNA.